The Boundary of Alkali Surface Boundary Exospheres of Mercury and the Moon. Issue 16 (12th August 2020) - Sarantos, M.; Tsavachidis, S.
Abstract: Global exosphere models of alkali gases surrounding Mercury and the Moon assume that the primary effect of the porous soil is to reduce the effective desorption rates. We demonstrate with a kinetic simulation that, following adsorption, the complicated structure of soils has two additional effects on the fate of previously released alkali atoms: (1) trapping of free atoms at lunar temperatures by microscopic shadows and inward diffusion, which becomes the primary sink mechanism, and (2) high‐energy barriers for thermal desorption compared to what would be retrieved from experiments on thin films or compacted pellets, especially when surface diffusion of adsorbates is considered. Lunar soils retain one fifth to two thirds of recycled adsorbates, depending on the assumed adsorbate mobility, photodesorption cross section, and soil thermal gradient. A transition from a retentive surface to full outgassing at T  > 500 K will produce complex feedback mechanisms of alkali circulation at Mercury. Plain Language Summary: This paper seeks to understand physical processes that occur on mineral surfaces throughout the Solar System and which affect the atmospheres of Mercury and the Moon. When meteoroids and the solar wind impact the surface, they vaporize sodium and potassium atoms, some of which cannot escape the body's gravity and can populate the atmosphere with successive bounces until they are lost to space via ionization, react with the surface, or penetrate into the soil. We quantify the competition between evaporation and diffusion within the top 1 mm of the soil, which supports the atmosphere reservoir, by following test particle trajectories in soils simulated with a sphere packing code. The simulations provide empirically constrained insights about the longevity of these free atoms. These findings provide context for understanding observations from ground‐based telescopes, MESSENGER and LADEE observations, and laboratory experiments and pave the way for higher‐fidelity models of exospheres for these species. Key Points: We modeled processes occurring on very different timescales in the soil of Mercury and the Moon Microscopic shadows trap up to half of the deposited sodium and potassium atoms at lunar temperatures Desorption of previously trapped atoms at higher temperatures could induce additional feedback in Mercury sodium circulation models